TINGKAT KOLONISASI PERAKARAN BIBIT PISANG JANTAN YANG DIINOKULASI DENGAN BEBERAPA DOSIS INOKULAN FUNGI MIKORIZA ARBUSKULA SERTA LAMA PEMBERIAN FOSFAT - Novi, Novi; Rizki, Rizki (Jurnal Pelangi : Research of Education and Development, 2014)
Male banana is one of the varieties of bananas that becomes a main commodity of West Sumatra. As a main commodity, then growth, quality and productivity need to be maintained and improved. Soil microbial technology application, such as the development of biological agents of Fungi Mycorrhizae Fungi (AMF), is one of the strategies need to be tested and developed to support the development of a national program of healthy banana seedlings as well as issues of pressing environmental preservation based fertilizers and chemical pesticides. This research was conducted at the Laboratory of Plant Physiology and tissue culture and greenhouse of Faculty of Agriculture, University of Andalas, Padang. This research used an experimental method arranged in a factorial completely-randomized design consisting of two factors with three replications. Factor A: Dose mycorrhizae (A0 = no inoculation, A1 = 5 g inoculant FMA PU10, A2 = 10 g inoculant FMA PU10, A3 = 15 g inoculant PU10, A4 = 20 g inoculant PU10. Factor B: Timing of phosphate (B0 = 0 HSI inoculant FMA PU10 B1 = 10 HSI inoculant FMA PU10, B2 = 20 HSI inoculant FMA PU10, B3 = 30 HSI inoculant FMA PU10, B4 = 40 HSI inoculant FMA PU10). The research shows that inoculation of inoculant FMA on different doses give a significant effect on the percentage of male banana seedling of root colonization. Where dosing 10 grams (A2) shows that the highest root colonization percentage compared with other treatments equals to 53. 33%. The provision of phosphate on 30th day of  HSI Mycorrhizae shows that the highest percentage of colonization is 45.55%.